Sustainability-Integrated Ecology Lessons: Effects on Students' Conceptual Understanding, Attitudes and Perceptions Toward Sustainable Development - Erdee Cajurao; Irene Cajurao; Ralito C. Jamora, Jr. (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: This study investigated the impact of sustainability-integrated lessons in ecology on Grade 11 students' conceptual understanding, attitudes, and perceptions toward sustainable development. Methodology: An explanatory sequential mixed-methods design was employed, involving quantitative data collection followed by qualitative exploration. A purposive sampling technique was used to select one intact class of 38 Grade 11 students, ensuring that both male and female students were represented. Pre- and post-tests assessed students' conceptual understanding, while attitude scales measured shifts in sustainability attitudes. Qualitative data, gathered from student-written journals, provided insights into personal reflections and behavioral intentions. Main Findings: Results demonstrated significant (p<0.001) gains in students' conceptual understanding and attitudes toward sustainability, regardless of gender. Qualitative analysis revealed students' increased sense of personal responsibility, community involvement, and environmental awareness. Novelty/Originality of this study: The present study addresses a gap in the local curriculum by investigating the impact of lessons that integrate sustainability principles into ecology education. The study findings underscore the value of embedding sustainability concepts in ecology education through active and experiential learning, fostering knowledge, positive attitudes, and a commitment to sustainable practices among students, empowering them to be proactive environmental stewards in their communities.